ANALISIS ANGGARAN DAN PROFITABILITAS SEBAGAI ALAT BANTU MANAJEMEN GUNA MENGOPTIMALKAN LABA - Mona Permatasari Mokodompit; Isabela Fenty Muliyawati Matatula; Hustianto Sudarwadi (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2020)
This research is a case study research conducted at CV Tintur Jaya in Manokwari regency. The purpose of the research is to analyze the budget set by the company in optimizing profits and to analyze the level of profitability achieved by the company. The research data are financial statements of CV Tintur Jaya withink three years which were analyzed using difference analysis and profitability analysis. The results has shown that as a whole the use of CV Tintur Jaya’s budget has been effiecient as a management tool in optimizing company profits, where there is a favorable difference between the company’s budget and realization. In addition, the level of profitability acchieved by the company within three years experienced a fluctuating ratio growth.